Assessment of the Risk of Depression in Residents Staying at Long-Term Care Institutions in Poland During the COVID-19 Pandemic Depending on the Quality of Cognitive Functioning - Górski, Michał; Buczkowska, Marta; Grajek, Mateusz; Garbicz, Jagoda; Całyniuk, Beata; Paciorek, Kamila; Głuszek, Aleksandra; Polaniak, Renata (Frontiers in Psychology, 2022)
Background: The development of the COVID-19 pandemic has prompted the implementation of many procedures to safeguard against further increases in illness. Unfortunately, this has drastically reduced patients' contact with their families, which has increased feelings of loneliness and isolation. This is particularly difficult in long-term care facilities, where the risk of developing depression is higher than in the general population. Objectives: The aim of the study was to assess the risk of depression among the residents of long-term care institutions in Poland during the COVID-19 pandemic and to determine the relationship between the risk of depression and the occurrence of cognitive impairment in the study group. Methods: The study included 273 patients from long-term care institutions in Poland. The risk of depression was determined based on an originally designed questionnaire. The cognitive state of the subjects was assessed using the screening test Mini-Mental State Examination (MMSE). Both the depression risk assessment and the MMSE test were conducted twice: in March and December 2020. Results: In March, severe dementia was present in 28.2% of the patients and normal MMSE scores were observed in 16.1% of the subjects; in December, the prevalence of severe dementia increased to 31.1% and that of normal scores decreased to 10.3%. In March, no patient was found to be at high risk of depression and moderate risk was observed in 14.3% of the subjects; in December, 2.6% of the patients had a high risk score and 45.4% had a moderate risk score. Statistical analysis revealed that higher MMSE scores correspond with a higher risk of depression. Conclusions: A higher risk of depression was observed with the development of the pandemic. Patients with cognitive impairment were characterised by a lower risk of depression compared to individuals with normal MMSE scores. During the study, progression of cognitive impairment was observed in the patients.